Medication adherence of diabetic and hypertensive patients attending primary health care centers: Cross-sectional study in Morocco - Samira Essoli; Latifa Adarmouch; Adil Mansouri; Sarah Michaud; Majda Sebbani; Mohamed Amine (Chronic Diseases Journal)
BACKGROUND: Medication adherence is a key factor in controlling chronic diseases, particularly diabetes and high blood pressure. We aimed to describe the level of medication adherence of patients with diabetes or high blood pressure in urban and rural areas in Morocco and to identify the factors associated with medication non-adherence.